Re-examination of Turkey red - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2007)
Cotton yam was dyed in Turkey red using madder through a special method. Amount of the dyestuffs bound to mordanted cotton fibre and the oiling numbers of the cotton yarn was investigated by using TLC (thin layer chromatography) and spectrophotornetry. Sn(II) in the bright red cotton yarn was analysed by X-ray diffraction method.